Monopoly without a Monopolist: An Economic Analysis of the Bitcoin Payment System. (31st March 2021) - Huberman, Gur; Leshno, Jacob D; Moallemi, Ciamac
Abstract: Bitcoin provides its users with transaction-processing services which are similar to those of traditional payment systems. This article models the novel economic structure implied by Bitcoin's innovative decentralized design, which allows the payment system to be reliably operated by unrelated parties called miners. We find that this decentralized design protects users from monopoly pricing. Competition among service providers within the platform and free entry imply no entity can profitably affect the level of fees paid by users. Instead, a market for transaction-processing determines the fees users pay to gain priority and avoid transaction-processing delays. The article (i) derives closed-form formulas of the fees and waiting times and studies their properties, (ii) compares pricing under the Bitcoin Payment System to that under a traditional payment system operated by a profit-maximizing firm, and (iii) suggests protocol design modifications to enhance the platform's efficiency. The Appendix describes and explains the main attributes of Bitcoin and the underlying blockchain technology.